Study of the influence between the strength of antibending of working rolls on the widening during hot rolling of thin sheet metal (Fracture and Structural Integrity, 2016)
Based on the variation principle of Jourdan was developed a mathematical model of the process of widening freely in hot rolling of thin sheet metal. The principle applies to rigid-plastic materials and for the cinematically admissible area of speeds. The developed model allows to study the distribution of the widening on the length of the deformation zone depending on the parameters of the rolling process and sheet metal. Results are obtained, characterizing the size of the widening and effectiveness of the process control on tension at the entrance and exit from the stand. The widening is dependent on the strength of anti bending.
Keywords: Hot rolling